One concept does not fit all: the immune system in different forms of acute kidney injury. Issue 1 (26th April 2020) - Anders, Hans-Joachim; Wilkens, Louise; Schraml, Barbara; Marschner, Julian
Abstract: Renal and immune systems maintain body homoeostasis during physiological fluctuations and following tissue injury. The immune system plays a central role during acute kidney injury (AKI), adapting evolutional systems programmed for host defence and minimizing unnecessary collateral damage. Indeed, depending upon the disease context, the impact of the immune system upon the manifestations and consequences of AKI can be quite different. Here we provide an overview of the known and unknown involvement of the immune system within the wide range of different forms of AKI, to oppose oversimplification and to endorse deeper insights into the pathogenesis of the different diseases causing kidney injury. This approach may help to overcome some of the current hurdles in translational AKI research and the development of specific treatments for the different diseases, all presenting with an acute increase in serum creatinine or decline in urinary output. One concept does not fit all.